Design of a hydraulic servo-actuation fed by a regenerative braking system. (1st February 2017) - Pugi, L.; Pagliai, M.; Nocentini, A.; Lutzemberger, G.; Pretto, A.
Highlights: An innovative on board hydraulic system fed by a KERS is presented. A complete model of the proposed system is presented. The model is validated on experimental data. Abstract: Many conventional truck and working machines are equipped with additional hydraulic tooling or manipulation systems which are usually fed through a mechanical connection with the internal combustion engine, involving a poor efficiency. In particular, this is a common situation for industrial vehicles whose mission profiles involves a relevant consumption of energy by the on board hydraulic systems, respect to the one really needed for only traction purpose. In this work it is proposed an innovative solution based on the adoption of a system aimed to recover braking energy in order to feed an efficient on board hydraulic actuation system. The proposed system is then adopted to a real application, an Isuzu truck equipped with a hydraulic tooling for garbage collection. A prototype of the system has been designed, assembled and tested showing a relevant improvement of system efficiency and the feasibility of the proposed approach. In the paper the proposed solution is presented, showing the simulation models and preliminary validation results including experimental devices assembled to perform the tests.